THE EFFECT OF USING TWO STAY TWO STRAY (TS-TS) TECHNIQUE TOWARD THE STUDENTS‟ READING COMPREHENSION OF NARRATIVE TEXT AT XI GRADE IN SMAN 2 KUOK KAMPAR REGENCY - Nesa Isnaniah (Journal of English Language and Education, 2019)
The aim of this research is to find out the effectiveness of the use of two stay-two stray in teaching reading comprehension on narrative text. This research was conducted to the eleventhgrade students of SMAN 2 Kuok in academic year 2016/2017. In this research, a quasi-experimental research with post test only was used by the writer. The samples of this research were class XI IPA 1 as the control group and class XI IPS 1 as the experimental group. The data were collected through post-test by using multiple-choice test items. The items are thirty question. Based on the data analysis of the research showed that the average students post test in experimental class were 75.44, and in control class has average students post test were in post test 71.12. So, the difference average is 4.32. The researcher used t-test, the results of the average test calculation (t-test) tcount3,63 and ttable 1,68. Therefore, concluded that there was a positive effect in learning reading comprehension of narrative text by using Two Stay Two Stray in experimental class at XI grade of SMAN 2 Kuok than control class.